Influence Brand Trust, Word of Mouth, Price, Brand Image, Product Quality, and Location against the Purchase Decision on Coffee Shop in Batam City - Saputra, Suyono; Hernandez, Louis (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Nowadays, everyone knows the name Coffee Shop, from young people to old people. This research was conducted to identify the influences of Brand Trust, WOM, Price, Brand Image, Product Quality, and location on Consumer Satisfaction and Purchasing Decisions. The population taken was all the people of Batam City who had been to a Coffee Shop in Batam City. The data collection process in this research obtained primary data using data collection techniques in the form of distributing questionnaires to respondents via Google Forms. The method used to analyze this research uses IBM SPSS PLS Statistics software with the application of descriptive analysis, quantitative analysis, and classical assumption tests. From the research results it was found that Brand Trust, WOM, Price, Brand Image, Product Quality, and location significantly influence consumer satisfaction and purchasing decisions. Consumer satisfaction significantly influences purchasing decisions.